A Theoretical Study of Realist and Liberal in Nepal-India Relationship: Examining the Complex Historical and Current Dynamics of Nepal-India Relationship (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The relationship between Nepal and India has several facets, including historical, social,political, and cultural. Open borders and people-to-people familial and cultural exchanges are hallmarksof the friendship and cooperation between the two countries. As a starting point, we examine theproblems in the historical narratives that portray Nepal-India ties as founded on mutual respect for eachother's sovereignty, which not only risks establishing stereotypes but also leaves it incomplete andmisleading. Though some parts of Nepal-India ties extend back to before the contemporary nation-state,any history of these connections which fails to acknowledge India as a hegemon that interferes inNepal's internal affairs and blocks Nepal's social, economic, and political development is incomplete.From a neocolonial perspective, we show how India has infringed on Nepal's sovereignty andindependence in many ways and circumstances. Nepal and India have also exchanged high-level visits.In 2015, Nepal enacted a new constitution and put it into effect. However, India placed a unilateralboycott because it was unhappy with some of the content. It was later normalised between Nepal andIndia and the Limpiyadhura-Lipulekh boundary dispute resurfaced. The most important question is whathas happened to the historical ties that were based upon? This study examines the historicalrelationship between India and Nepal, as well as the current state of affairs.